THE EFFECT OF INQUIRY-BASED LEARNING (IBL) ON STUDENTS’ ENGAGEMENT AND CRITICAL THINKING SKILLS IN AN EFL CLASSROOM: A QUASI-EXPERIMENTAL STUDY - Sri Wahyuni; Nur Hidayat; Davron Aslonqulovich Juraev; Muhammad Arief Budiman (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
English as a Foreign Language (EFL) learning continues to face challenges in enhancing student engagement and developing critical thinking skills required in the 21st century. This study investigates the effect of Inquiry-Based Learning (IBL) on students’ engagement and critical thinking skills in an English as a Foreign Language (EFL) classroom. Employing a quasi-experimental design with a non-equivalent control group, the research involved 56 undergraduate students (in Universitas PGRI Semarang) divided into a control group (n = 28) and an experimental group (n = 28). The experimental group received instruction through the Inquiry-Based Learning approach for one semester, while the control group was taught using conventional teacher-centered methods. Data were collected using a Student Engagement Questionnaire measuring behavioral, emotional, and cognitive engagement, as well as a Critical Thinking Test to assess students’ higher-order thinking skills. Both groups completed pre-tests and post-tests to examine changes before and after the intervention. The data were analyzed using descriptive and inferential statistics to determine significant differences between groups. The findings indicate that students exposed to Inquiry-Based Learning demonstrated higher levels of engagement and significantly improved critical thinking skills compared to those in the control group. These results suggest that IBL is an effective pedagogical approach for fostering active learning and higher-order thinking in EFL contexts. ABSTRAK Pembelajaran bahasa Inggris sebagai bahasa asing (EFL) masih menghadapi tantangan dalam meningkatkan keterlibatan mahasiswa dan mengembangkan keterampilan berpikir kritis yang diperlukan pada abad ke-21. Penelitian ini menyelidiki pengaruh Inquiry-Based Learning (IBL) terhadap keterlibatan siswa dan keterampilan berpikir kritis dalam kelas English as a Foreign Language (EFL). Dengan menggunakan desain kuasi-eksperimen dengan kelompok kontrol non-ekuivalen, penelitian ini melibatkan 56 mahasiswa (di Universitas PGRI Semarang) yang dibagi menjadi kelompok kontrol (n = 28) dan kelompok eksperimen (n = 28). Kelompok eksperimen menerima pembelajaran melalui pendekatan Inquiry-Based Learning selama satu semester, sedangkan kelompok kontrol diajar menggunakan metode konvensional yang berpusat pada guru. Data dikumpulkan menggunakan Kuesioner Keterlibatan Siswa yang mengukur keterlibatan perilaku, emosional, dan kognitif, serta Tes Berpikir Kritis untuk menilai keterampilan berpikir tingkat tinggi mahasiswa. Kedua kelompok mengikuti pre-test dan post-test untuk mengamati perubahan sebelum dan sesudah intervensi. Data dianalisis menggunakan statistik deskriptif dan inferensial untuk menentukan perbedaan signifikan antar kelompok. Hasil penelitian menunjukkan bahwa mahasiswa yang mengikuti pembelajaran berbasis Inquiry-Based Learning menunjukkan tingkat keterlibatan yang lebih tinggi dan peningkatan keterampilan berpikir kritis yang signifikan dibandingkan dengan mahasiswa pada kelompok kontrol. Temuan ini menunjukkan bahwa IBL merupakan pendekatan pedagogis yang efektif untuk mendorong pembelajaran aktif dan keterampilan berpikir tingkat tinggi dalam konteks EFL.